Frequency Spectrum and Wavelet Packet Analyses of Blasting Vibration Signals for Different Charge Structures in Blasting Peripheral Holes - Ke Man; Xiaoli Liu; Zhifei Song (Advances in Civil Engineering)
Based on the blasting principle of the cutting seam cartridge, smooth blasting with the charge structures of the usual cartridge and cutting seam cartridge has been designed and implemented, respectively, for different peripheral holes in the same face. Meanwhile, the blasting vibration has been monitored. Through the analysis of the frequency spectrum of blasting vibration signals, it is found that the maximum blasting vibration velocity of the cutting seam cartridge charge is lower than that of the usual cartridge charge, from 0.21 m/s to 0.12 m/s. Moreover, the blasting energy distribution is more balanced. Especially in the low-frequency part, the blasting energy is less, and there is a transferring trend to the high-frequency part, which shows that the cutting seam cartridge charge has a better optimization effect. Furthermore, using wavelet packet analysis, the cutting seam cartridge charge could effectively reduce the energy concentration in the low-frequency part. The energy distribution is much more dispersed, and the disturbance to the structure could be less, which is conducive to the stability of the structure. According to the blasting effect, the overbreak and underexcavation quantity at the cutting seam cartridge charge is better than that at the usual cartridge charge.